2002
DOI: 10.1007/s10350-004-6332-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Radiotherapy for Primary Resectable Rectal Adenocarcinoma on Male Sexual and Urinary Function

Abstract: Preoperative radiotherapy for primary resectable rectal carcinoma treated by total mesorectal excision with autonomic nerve preservation may impair male sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 24 publications
3
49
1
6
Order By: Relevance
“…Despite these shortcomings, our data suggest that, in spite of better visualization of the autonomic nerves, the occurrence of neurogenic sexual dysfunction and LUTS after LTME are comparable to the results found in studies after OTME [1,2].…”
Section: Discussionsupporting
confidence: 77%
“…Despite these shortcomings, our data suggest that, in spite of better visualization of the autonomic nerves, the occurrence of neurogenic sexual dysfunction and LUTS after LTME are comparable to the results found in studies after OTME [1,2].…”
Section: Discussionsupporting
confidence: 77%
“…The rate of LR after ISR varies from 0% to 22.7%, lower than that after APR (10–57%) for mid or low rectal cancer 27, 31, 67. Neoadjuvant CRT affects the down‐sizing of tumor and down‐staging of disease, and is often used as a standard strategy to avoid a positive CRM and LR in rectal cancer patients 68, 69, 70, 71, 72. However, some questions remain as to whether neoadjuvant CRT should be more widely applied for patients who would undergo ISR.…”
Section: Discussionmentioning
confidence: 99%
“…However, some questions remain as to whether neoadjuvant CRT should be more widely applied for patients who would undergo ISR. CRT is associated with higher surgical complications,68, 69 a negative impact on anal function,45, 70 and sexual disorder,71 and has no clear survival benefit 72. In Japan, preoperative neoadjuvant CRT has not been routinely carried out for resectable T1, T2 and T3 tumors regardless of the presence or absence of lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the series of Bonnel et al [50] sexual function was altered more in those patients who received preoperative pelvic radiotherapy than those who underwent surgery alone. Spontaneous erection, stimulated erection, and rigidity of erection were unchanged between the two groups.…”
Section: Male Sexual Dysfunctionmentioning
confidence: 94%
“…Microscopic changes include fibrosis of the nerve sheath with demylination and fibrous replacement of the nerve fibers. It has been suggested that the fibrosis causes nerve entrapment with secondary demylination and vascular injury [50]. Pelvic radiation can also lead to fibrosis of the seminal vesicles, impairing their normal function.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%